N-Myristoylation by NMT1 Is POTEE-Dependent to Stimulate Liver Tumorigenesis via Differentially Regulating Ubiquitination of Targets - Zhu, Guoqing; Wang, Feng; Li, Haojie; Zhang, Xiao; Wu, Qi; Liu, Ya; Qian, Mingping; Guo, Susu; Yang, Yueyue; Xue, Xiangfei; Sun, Fenyong; Qiao, Yongxia; et al. (Frontiers in Oncology, 2021)
Background: Tremendous studies have suggested that post-translational modifications (PTMs) play pivotal roles during tumorigenesis. Compared to other PTMs, lipid modification is less studied. Recently, N-myristoylation, one type of lipid modification, has been paid attention to the field of cancer. However, whether and how N-myristoylation exerts its roles in liver tumorigenesis still remains unclear. Methods: Parallel reaction monitoring (PRM) was conducted to evaluate the expression of protein modification enzymes in paired tissues. liver conditionally knocking NMT1 out mice model was used to assess the critical roles of N-myristoylation during liver tumorigenesis. Proteomics isobaric tags for relative and absolute quantification (iTraq) was performed to identify proteins that changed while NMT1 was knocked down. The click chemistry assay was used to evaluate the N-myristoylation levels of proteins. Results: Here, N-myristolyation and its enzyme NMT1 but not NMT2, were found to be critical in liver cancer. Two categories of proteins, i.e. N-myristolyation down-regulated protein (NDP) and N-myristolyation up-regulated protein (NUP) were revealed negatively and positively regulated by NMT1, respectively. Both NDP and NUP could be N-myristolyated by NMT1 indispensible of POTEE. However, N-myristolyation decreased and increased stability of NDP and NUP, respectively. Mechanistically, NDP-specific binding protein RPL7A facilitated HIST1H4H, which has ubiquitin E3 ligase function, to ubiquitinate NDP. By contrast, NUP-specific binding protein HBB prevented NUP from ubiquitination by HIST1H4H. Notably, function of RPL7A and HBB were all NMT1-dependent. Moreover, NDP suppressed while NUP stimulated transformative phenotypes. Clinically, higher levels of NMT1 and NUP with lower levels of NDP had worse prognostic outcome. Conclusion: Collectively, N-myristolyation by NMT1 suppresses anti-tumorigenic NDP, whereas stimulates pro-tumorigenic NUP by interfering their ubiquitination to finally result in a pro-tumorigenic outcome in liver cancer. Targeting N-myristolyation and NMT1 might be helpful to treat liver cancer.